A preparation method for 3D printing tungsten alloy

By using multiple mixing and laser printing techniques of Nifecom powder and tungsten powder in additive manufacturing, to prepare tungsten alloy with BCC phase, FCC phase and L12 phase, solving the strength and toughness of tungsten alloy in existing technology that do not match the strength and toughness of toughness in the existing technologies that do not match the strength and toughness of the tungsten alloy. The problem realizes the preparation of tungsten alloy with high strong toughness.

CN118720162BActive Publication Date: 2025-01-24CENT SOUTH UNIV

Patent Information

Application Number
CN202410771634.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-15
Publication Date
2025-01-24
Estimated Expiration
2044-06-15

AI Technical Summary

Technical Problem

In the prior art, the strength and toughness of additively manufactured tungsten alloys do not match, making it difficult to meet the high strength and toughness requirements required for kinetic energy damage.

Method used

After mixing Ni, FE, CO, and M, the ball milling is performed, and Nifecom powder is obtained, and tungsten powder and Nifecom powder are printed multiple times and laser printing to prepare tungsten alloy with BCC phase, FCC phase and L12 phase.

Benefits of technology

The uniformity and high strong toughness of the tungsten alloy turtle alloys are achieved, and the combination of tungsten particles in traditional tungsten alloy and the combination of adhesion is not close, and the tensile performance and toughness are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118720162B_ABST
    Figure CN118720162B_ABST
Patent Text Reader

Abstract

The present invention provides a preparation method of 3D printed tungsten alloy, belonging to the technical field of metal materials. The present invention firstly mixes Ni, Fe, Co and M and then performs ball milling to obtain NiFeCoM powder, wherein M contains one or more of Al, V and Nb; then the tungsten powder and NiFeCoM powder are sequentially mixed for the first time, mixed for the second time and laser printed to obtain tungsten alloy. The tungsten alloy prepared by the present invention has uniform structure and composition, without obvious element segregation, and generates nano-scale L1 coherent with FCC phase and semi-coherent with BCC phase. 2 Phase, L1 2 The formation of phase realizes the precipitation strengthening of tungsten alloy and improves the tensile properties and toughness of tungsten alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal materials, and in particular to a method for preparing a 3D printed tungsten alloy. Background Art

[0002] High-density tungsten alloy has high density, good room temperature and high temperature strength, creep resistance, and high thermal conductivity, making it an ideal material for armor-piercing projectile cores. The current mechanical processing of tungsten alloys has problems such as difficult product processing, poor processability, and unstable product quality; at the same time, complex structure cores are connected by split threads and adhesives, and the overall consistency of the product is not strong, which seriously limits the performance of armor-piercing projectiles. Therefore, with the increasing thickness of armor and the level of protection, the complexity of three-dimensional structures and integrated tungsten alloys have become an important trend and urgent need in the development of armor-piercing projectile cores, and there is an urgent need for high-density tungsten alloys with high strength, toughness, and self-sharpening properties that are integrated with additive manufacturing.

[0003] In the traditional W-Ni-Fe high-density tungsten alloy additive manufacturing process, due to the non-equilibrium supersolid solution of W in the (Ni, Fe) binder phase and the non-uniform reaction and precipitation of W and Ni / Fe elemental elements, complex microstructures and a large number of intermetallic compound phases are easily generated in the alloy, resulting in the toughness of the tungsten alloy being only 1 / 5 of that of the alloy prepared by liquid phase sintering, which makes it difficult to meet the requirements of high strength and toughness matching required for kinetic energy damage.

[0004] The FCC structured high entropy alloy has strong adiabatic shearing ability and excellent plasticity. It has attracted widespread attention as a tungsten alloy binder phase with great potential for armor-piercing projectiles. At the same time, the FCC structured high entropy alloy is not easy to react with W to form intermetallic compounds during the additive manufacturing process, and is very suitable for the preparation of high-strength and tough tungsten alloys. However, during the additive manufacturing process, the heating and cooling are rapid, and the elements do not have time to fully diffuse. Therefore, the uniformity of the mixed powder determines the uniformity of the organization and composition of the printed tungsten alloy sample. At the same time, designing the alloy element ratio and adjusting the printing process parameters will greatly affect the performance of the tungsten alloy. Therefore, it is of great significance to study a preparation method for 3D printed tungsten alloys to improve the tensile properties and toughness of tungsten alloys. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation method of 3D printed tungsten alloy to solve the problem of mismatch between strength and toughness of tungsten alloy manufactured by additive manufacturing in the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing 3D printed tungsten alloy, comprising the following steps:

[0008] (1) Ni, Fe, Co and M are mixed and ball-milled to obtain NiFeCoM powder;

[0009] The M comprises one or more of Al, V and Nb;

[0010] (2) Tungsten powder and NiFeCoM powder are sequentially mixed for the first time, mixed for the second time and laser printed to obtain tungsten alloy.

[0011] Preferably, in step (1), the atomic ratio of Ni, Fe, Co and M is 1.0-4.5:0.5-2.5:0.5-2.5:0.1-2.5.

[0012] Preferably, in step (1), the ball-to-material ratio of the ball milling treatment is 1:1-5, the rotation speed of the ball milling treatment is 50-350 rpm, and the ball milling treatment time is 20-60 min.

[0013] Preferably, in step (2), the mass ratio of tungsten powder to NiFeCoM powder is 75-90:10-25.

[0014] Preferably, in step (2), the rotation speed of the first mixing is 140 to 160 rpm, and the time of the first mixing is 2 to 6 hours.

[0015] Preferably, in step (2), the rotation speed of the second mixing is 50 to 150 rpm, and the time of the second mixing is 5 to 10 min.

[0016] Preferably, in step (2), the laser printing power is 900-1800 W, the speed is 100-800 mm / min, the single layer thickness is 0.4-0.6 mm, and the scanning interval is 0.8-1.2 mm.

[0017] Beneficial effects of the present invention:

[0018] (1) The tungsten alloy prepared by the present invention has uniform composition and no obvious element segregation. The alloy has BCC phase, FCC phase and L12 phase. The nanoscale L12 phase is coherent with the FCC phase and semi-coherent with the BCC phase. There is no intermetallic compound between the tungsten particles and the bonding phase, and the connection is tight. The formation of the L12 phase realizes precipitation strengthening of the tungsten alloy and improves the tensile properties and toughness of the tungsten alloy.

[0019] (2) The present invention prepares tungsten alloy by laser directed energy deposition method, realizes liquid phase sintering and non-equilibrium solidification of alloy elements, obtains non-equilibrium precipitation phase, adjusts the organizational structure of tungsten alloy by adjusting laser power and scanning speed, thereby promoting high-strength connection between tungsten particles and bonding phase, obtains coherent / incoherent precipitation phase strengthening bonding phase, and obtains high-density and high-strength tungsten alloy. It overcomes the shortcomings of the prior art that tungsten particles and bonding phase are not tightly combined and the bonding phase has low strength, and realizes the preparation of tungsten alloy with high entropy alloy as bonding phase.

[0020] (3) The tungsten alloy prepared by the present invention can be used in the fields of military industry, nuclear industry, aerospace, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a tensile mechanics curve diagram of the W-NiFeCoNbAlV alloy of Example 1;

[0022] Figure 2 This is a tensile fracture morphology of the W-NiFeCoNbAlV alloy of Example 1;

[0023] Figure 3 is a morphology diagram of the W-NiFeCoNbAlV alloy of Example 2;

[0024] Figure 4 is a tensile mechanics curve diagram of the W-NiFeCoNbAlV alloy of Example 2;

[0025] Figure 5 is a tensile mechanics curve diagram of the W-NiFeCoAlV alloy of Example 3;

[0026] Figure 6 This is a tensile fracture morphology of the W-NiFeCoAlV alloy of Example 3;

[0027] Figure 7 This is the tensile mechanics curve of the W-NiFeCoAlV alloy of Example 4. DETAILED DESCRIPTION

[0028] The present invention provides a method for preparing 3D printed tungsten alloy, comprising the following steps:

[0029] (1) Ni, Fe, Co and M are mixed and ball-milled to obtain NiFeCoM powder;

[0030] The M comprises one or more of Al, V and Nb;

[0031] (2) Tungsten powder and NiFeCoM powder are sequentially mixed for the first time, mixed for the second time and laser printed to obtain tungsten alloy.

[0032] In the present invention, when the M is preferably Al, Nb and V, the atomic ratio of Al, Nb and V is preferably 0.2-0.5:0.2:0.2; when the M is preferably Al and V, the atomic ratio of Al and V is preferably 0.2-0.5:0.2-0.5, preferably 0.2:0.2 or 0.5:0.5.

[0033] In the present invention, the Ni, Fe, Co and M are preferably spherical powders, and the particle size of the spherical powders is preferably 15 to 51 μm.

[0034] In the present invention, in step (1), the atomic ratio of Ni, Fe, Co and M is 1.0-4.5:0.5-2.5:0.5-2.5:0.1-2.5, preferably 1.5-3.0:1.0-2.0:1.0-2.0:0.2-2.0, and more preferably 2.0-2.5:1.5-2.0:1.4-1.8:0.4-1.5.

[0035] In the present invention, in the step (1), the ball-to-material ratio of the ball milling treatment is 1:1-5, preferably 1:2-4, and more preferably 1:2; the rotation speed of the ball milling treatment is 50-350rpm, preferably 60-300rpm, and more preferably 90-200rpm; the ball milling treatment time is 20-60min, preferably 30-50min, and more preferably 30-40min.

[0036] In the present invention, in the step (2), the mass ratio of tungsten powder to NiFeCoM powder is 75-90:10-25, preferably 75:25 or 85:15 or 90:10, and more preferably 85:15.

[0037] In the present invention, the tungsten powder is preferably a spherical tungsten powder with a particle size of 50-100 μm prepared by a rotating electrode atomization method. The tungsten powder used in the embodiment of the present invention was purchased from Xi'an Sailong Additive Technology Co., Ltd. and is a spherical tungsten powder (particle size of 50-100 μm).

[0038] In the present invention, in step (2), the rotation speed of the first mixing is 140 to 160 rpm, preferably 145 to 155 rpm, and more preferably 150 rpm; the time of the first mixing is 2 to 6 h, preferably 3 to 5 h, and more preferably 4 h.

[0039] In the present invention, the first mixing is carried out in a drum type mixing device, the air in the mixing tank is firstly evacuated to a low vacuum, and then argon is filled in as a protective atmosphere, and then the first mixing is carried out. The first mixing is carried out in an argon atmosphere to prevent the mixed powder from being oxidized.

[0040] In the present invention, in step (2), the rotation speed of the second mixing is 50 to 150 rpm, preferably 60 to 120 rpm, and more preferably 70 to 100 rpm; the time of the second mixing is 5 to 10 min, preferably 6 to 8 min, and more preferably 6 min.

[0041] In the present invention, the second mixing is preferably carried out in a zero-gravity mixer. The mixing in the zero-gravity mixer is to avoid uneven mixing of tungsten powder and NiFeCoM powder due to density differences.

[0042] The present invention adopts a two-time mixing method, firstly, the first mixing is carried out in a drum-type mixing device, and then the second mixing is carried out in a zero-gravity mixer, the purpose of which is to ensure that the powders are mixed evenly.

[0043] In the present invention, the laser printing is performed by using a laser directional energy deposition method, and the energy density formula is:

[0044]

[0045] In formula (1):

[0046] P——laser power, W;

[0047] v——speed, mm / min;

[0048] h——scanning distance, mm;

[0049] t——single layer thickness, mm.

[0050] In the present invention, the energy density is between 200 and 330 J / cm 3 When is the best.

[0051] In the present invention, in the step (2), the power during laser printing is 900-1800 W, preferably 1000-1700 W, and more preferably 1200-1600 W; the speed is 100-800 mm / min, preferably 200-600 mm / min, and more preferably 300-450 mm / min; the single layer thickness is 0.4-0.6 mm, and more preferably 0.5 mm; the scanning spacing is 0.8-1.2 mm, and more preferably 0.9-1.1 mm, and more preferably 1.0 mm.

[0052] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0053] Example 1

[0054] According to the atomic ratio of Ni:Fe:Co:Nb:Al:V=2.5:2:1.8:0.2:0.2:0.2, Ni powder, Fe powder, Co powder, Nb powder, Al powder and V powder (the particle size of the above powders is 15-51 μm, and all are spherical powders) are placed in a ball mill, and grinding balls are added according to the ball-to-material ratio of 1:2. The ball mill is treated at a speed of 90 rpm for 30 minutes to obtain NiFeCoNbAlV powder.

[0055] The air in the mixing tank was extracted to a low vacuum (vacuum degree of 5 Pa), and then filled with argon as a protective atmosphere. Tungsten powder (spherical tungsten powder with a particle size of 50-100 μm prepared by rotating electrode atomization method) and NiFeCoNbAlV powder were placed in the mixing tank at a mass ratio of 85:15, and the first mixing was carried out on a drum mixing equipment. The rotation speed of the first mixing was 150 rpm and the time was 4 hours.

[0056] Then the powder after the first mixing was transferred to a zero-gravity mixer for a second mixing, and the second mixing speed was 100 rpm and the time was 6 minutes.

[0057] The powder after the second mixing was printed using a laser directed energy deposition method. The printing process parameters were: printing single layer thickness t = 0.5 mm, scanning spacing h = 1.0 mm, laser power P = 1600 W, rate v = 450 mm / min, and a W-NiFeCoNbAlV alloy with a size of 30 mm × 25 mm × 18 mm was obtained.

[0058] The W-NiFeCoNbAlV alloy of Example 1 has uniform microstructure, and is organized into BCC phase, FCC phase and L12 phase. A unique cellular structure and nanoscale L12 phase are dispersed in the bonding phase. The Nb element is slightly enriched in the cellular structure, and together with the nanoscale L12 phase, it hinders the movement of dislocations, realizes the pinning of dislocations, and greatly improves the tensile strength of the tungsten alloy.

[0059] According to GB / T 228-2002 standard, tensile test was carried out on Instron 3369 universal testing machine (without extensometer), and the tensile rate was 0.45 mm / min. The tensile strength of W-NiFeCoNbAlV alloy was 1070 MPa (such as Figure 1 The fracture of the sample is mainly characterized by WW cleavage fracture (as shown in Figure 2 The density of the W-NiFeCoNbAlV alloy was 16.1 g / cm 3 The hardness value of W-NiFeCoNbAlV alloy tested by microhardness tester is 499HV.

[0060] Example 2

[0061] The difference from Example 1 is that Ni:Fe:Co:Nb:Al:V=2.5:2:1.8:0.2:0.5:0.2, and other conditions are the same, obtaining a W-NiFeCoNbAlV alloy.

[0062] The W-NiFeCoNbAlV alloy of Example 2 has uniform microstructure and is composed of BCC phase, FCC phase and L12 phase. The added Al absorbs a small amount of oxygen between the grains to form nano-scale aluminum oxide, which is dispersed in the binder phase (such as Figure 3 As shown in the figure, the strength of the alloy is improved, while the addition of Al also reduces the toughness of the W-NiFeCoNbAlV alloy.

[0063] According to GB / T 228-2002 standard, tensile test was carried out on Instron 3369 universal testing machine (with extensometer), and the tensile rate was 0.45 mm / min. The tensile strength of W-NiFeCoNbAlV alloy was 1020 MPa (such as Figure 4 The density of the W-NiFeCoNbAlV alloy was 15.6 g / cm 3 The hardness value of W-NiFeCoNbAlV alloy tested by microhardness tester is 460HV.

[0064] Example 3

[0065] According to the atomic ratio of Ni:Fe:Co:Al:V=2.5:2:1.8:0.2:0.2, Ni powder, Fe powder, Co powder, Al powder and V powder (the particle size of the above powders are all 15-51 μm, and all are spherical powders) are placed in a ball mill, and grinding balls are added according to a ball-to-material ratio of 1:2. The mixture is ball-milled at a speed of 200 rpm for 20 minutes to obtain NiFeCoAlV powder.

[0066] The air in the mixing tank was extracted to a low vacuum (vacuum degree of 5 Pa), and then filled with argon as a protective atmosphere. Tungsten powder (spherical tungsten powder with a particle size of 50-100 μm prepared by rotating electrode atomization method) and NiFeCoAlV powder were placed in the mixing tank at a mass ratio of 85:15, and the first mixing was carried out on a drum mixing equipment. The first mixing speed was 140 rpm and the time was 6 hours.

[0067] Then the powder after the first mixing was transferred to a zero-gravity mixer for a second mixing, and the second mixing speed was 50 rpm and the time was 10 min.

[0068] The powder after the second mixing was printed using a laser directed energy deposition method. The printing process parameters were: printing single layer thickness t = 0.5 mm, scanning spacing h = 1.0 mm, laser power P = 1600 W, rate v = 450 mm / min, and a W-NiFeCoAlV alloy with a size of 30 mm × 25 mm × 18 mm was obtained.

[0069] The W-NiFeCoAlV alloy of Example 3 has uniform microstructure, and the main structural phases are BCC phase, FCC phase and L12 phase. After reducing the Nb element, the dense cellular structure in the binder phase disappears, and the fracture toughness of the W-NiFeCoAlV alloy is improved.

[0070] According to GB / T 228-2002 standard, tensile test was carried out on Instron 3369 universal testing machine (with extensometer), and the tensile rate was 0.45mm / min. The tensile strength of tungsten alloy sample was 1010MPa, and the elongation was 9% (such as Figure 5 The fracture surface shows obvious W particle cleavage plane and bonding phase dimple structure (as shown in Figure 6 At the same time, the density of the W-NiFeCoAlV alloy was 15.4 g / cm 3 The hardness value of W-NiFeCoAlV alloy tested by microhardness tester is 480HV.

[0071] Example 4

[0072] According to the atomic ratio of Ni:Fe:Co:Al:V=2.5:2:1:0.5:0.5, Ni powder, Fe powder, Co powder, Al powder and V powder (the particle size of the above powders are all 15-51 μm, and all are spherical powders) are placed in a ball mill, and grinding balls are added according to a ball-to-material ratio of 1:5. The mixture is ball-milled at a speed of 200 rpm for 20 minutes to obtain NiFeCoAlV powder.

[0073] The air in the mixing tank was extracted to a low vacuum (vacuum degree of 5 Pa), and then filled with argon as a protective atmosphere. Tungsten powder (spherical tungsten powder with a particle size of 50-100 μm prepared by rotating electrode atomization method) and NiFeCoAlV powder were placed in the mixing tank at a mass ratio of 90:10, and the first mixing was carried out on a drum mixing equipment. The first mixing speed was 140 rpm and the time was 6 hours.

[0074] Then the powder after the first mixing was transferred to a zero-gravity mixer for a second mixing, and the second mixing speed was 50 rpm and the time was 10 min.

[0075] The powder after the second mixing was printed using a laser directed energy deposition method. The printing process parameters were: printing single layer thickness t = 0.5 mm, scanning spacing h = 1.0 mm, laser power P = 1600 W, rate v = 450 mm / min, and a W-NiFeCoAlV alloy with a size of 30 mm × 25 mm × 18 mm was obtained.

[0076] The W-NiFeCoAlV alloy of Example 4 has uniform microstructure, and the main structural phases are BCC phase, FCC phase and L12 phase. After removing the Nb element, the dense cellular structure in the bonding phase disappears. After increasing the Al and V contents, the fracture strength of the W-NiFeCoAlV alloy increases, but the fracture toughness decreases slightly.

[0077] According to GB / T 228-2002 standard, tensile test was carried out on Instron 3369 universal testing machine (with extensometer), and the tensile rate was 0.45mm / min. The tensile strength of tungsten alloy sample was 1084MPa, and the elongation was 6.9% (such as Figure 7 At the same time, the density of the W-NiFeCoAlV alloy was 14.4 g / cm 3 The hardness value of W-NiFeCoAlV alloy tested by microhardness tester is 500HV.

[0078] It can be seen from the above embodiments that the present invention provides a method for preparing 3D printed tungsten alloy, firstly, Ni, Fe, Co and M are mixed and ball milled to obtain NiFeCoM powder, wherein M contains one or more of Al, V and Nb; then tungsten powder and NiFeCoM powder are sequentially mixed for the first time, mixed for the second time and laser printed to obtain tungsten alloy. The tungsten alloy prepared by the present invention has uniform alloy structure composition, no obvious element segregation, and generates a nano-scale L12 phase that is coherent with the FCC phase and semi-coherent with the BCC phase. The generation of the L12 phase realizes precipitation strengthening of the tungsten alloy and improves the tensile properties and toughness of the tungsten alloy.

[0079] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing 3D printed tungsten alloy, characterized in that: The steps include: (1) Ni, Fe, Co and M are mixed and ball-milled to obtain NiFeCoM powder; The M is Al, Nb and V, or Al and V. When M is Al, Nb and V, the atomic ratio of Al, Nb and V is 0.2-0.5:0.2:0.

2. When M is Al and V, the atomic ratio of Al and V is 0.2-0.5:0.2-0.

5. (2) sequentially performing a first mixing, a second mixing and laser printing on tungsten powder and NiFeCoM powder to obtain a tungsten alloy; In the step (1), the atomic ratio of Ni, Fe, Co and M is 1.5-3.0:1.0-2.0:1.0-2.0:0.2-2.

0.

2. The preparation method according to claim 1, characterized in that: In the step (1), the ball-to-material ratio of the ball milling treatment is 1:1-5, the rotation speed of the ball milling treatment is 50-350 rpm, and the ball milling treatment time is 20-60 min.

3. The preparation method according to claim 2, characterized in that: In the step (2), the mass ratio of tungsten powder to NiFeCoM powder is 75-90:10-25.

4. The preparation method according to claim 1 or 3, characterized in that: In the step (2), the rotation speed of the first mixing is 140 to 160 rpm, and the time of the first mixing is 2 to 6 hours.

5. The preparation method according to claim 4, characterized in that: In the step (2), the rotation speed of the second mixing is 50 to 150 rpm, and the time of the second mixing is 5 to 10 minutes.

6. The preparation method according to claim 3 or 5, characterized in that: In the step (2), the laser printing power is 900-1800 W, the speed is 100-800 mm / min, the single layer thickness is 0.4-0.6 mm, and the scanning interval is 0.8-1.2 mm.

Citation Information

Patent Citations

  • Preparation method of fine-grain high-specific-gravity tungsten alloy

    CN109182871A

  • High-density tungsten alloy with high adiabatic shear sensitivity and high plasticity and preparation method of high-density tungsten alloy

    CN116240437A

Cited By

  • Preparation method of tungsten-copper composite material with layered structure

    CN121755728A